Integrated-system to minimizing cyber harassment in kingdom of Saudi Arabia (KSA) - Abdullah Moafa, Fahad; Ahmad, kamsuriah; Mugahed Al-Rahmi, Waleed; Yahaya, Noraffandy; Bin Kamin, Yusri; Alamri, Mahdi (International Journal of Engineering and Technology, 2018)
The proposed system framework consists two main databases: Lexicon dictionary and Summarized previous cases, by depending on Senti-ment analysis and N-Gram algorithms to match the terms and documents. In the first branch, the judge opens the cyber case and therefore the system will highlight the technical terms automatically. Furthermore, the technical terms matched with Lexicon dictionary will be high-lighted. After that, the judge opens the highlighted terms (as links), and description page will be appeared. The description page contains details about the technical terms (definitions, explanations, examples, etc). On the other side, the second branch aims to retrieve the related legal cases (from the database) judged by courts in UK and KSA. The related cases are the most closed cases to the current legal case by inserting keywords based on the current case. The judge benefits from these cases through the judgment issued to give the fair judgment. N-gram algorithm is used to find the related cases because it has smart approach to expect the most closed document and texts. The system provides the judge with laws used in issuing the judgment in KSA and UK courts.Â Â